STUDI PEMANFAATAN IKAN LELE DUMBO (Clarias gariepinus) DAN REBUNG (Dendrocalamus asper) DALAM PEMBUATAN SOSIS - Siswanti Siswanti; Netti Herawati; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The sausage is processed products that is very popular among the community. Type of sausages in the market are beef sausage and chicken sausage.Sausages that can be also made from catfish which has good nutritional value as well as a new product which is appreciated by the public. The purposes of the study was to obtain the best sausage formulations of dumbo catfish and bamboo shoot using the SNI quality standards. The research was conducted experimentally using completely randomized design (CRD) with five treatments and four repetitions, followed by DNMRT test at 5% level. The treatment in this study were LDR1 (ratio catfish 95and bamboo shoots 5) LDR2 (ratio catfish 90 and bamboo shoots 10) LDR3 (ratio catfish 85 and bamboo shoots 15) LDR4 (ratio catfish 80 and bamboo shoots 20) and LDR5 (ratio catfish 75 and bamboo shoots 25). Parameters observed were the moisture, ash, fat, protein, carbohydrates, crude fiber contants and sensory evaluation. Results of the analysis of variance showed the addition of catfish and bamboo shoot significanlyaffectedall parameters. The results of the study found that the best treatment was LDR4 with a value of 62,68% moisture content, 1,65%ash, 4,15% fat,13,48% protein, 18,04% carbohydrates and fiber content 2,49% and an overall assessment of sensory preferred by panellists.  Keywords :sausage, catfish, bamboo shoots.